An efficient reverse converter for the 4-moduli set {2^n -1, 2^n, 2^n + 1, 2^2n + 1} based on the new Chinese remainder theorem - Cao, Bin (2009)
The inherent properties of carry-free operations, parallelism and fault-tolerance have made the residue number system a promising candidate for high-speed arithmetic and specialized high-precision digital signal-processing applications. However, the reverse conversion from the residues to the weighted binary number has long been the performance bottleneck, particularly when the number of moduli set increases beyond 3. In